2021
DOI: 10.1038/s41388-021-01771-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of activating transcription factor 3 prevents KRAS-mediated pancreatic cancer

Abstract: The unfolded protein response (UPR) is activated in pancreatic pathologies and suggested as a target for therapeutic intervention. In this study, we examined Activating Transcription Factor 3 (ATF3), a mediator of the UPR which promotes acinar-to-ductal metaplasia (ADM) in response to pancreatic injury. Since ADM is an initial step in the progression to pancreatic ductal adenocarcinoma (PDAC), we hypothesized ATF3 is required for initiation and progression of PDAC. We generated mice carrying a germ line mutati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Activation Transcription Factor 3 (ATF3) is a stress-inducible transcription factor and member of the Hallmark p53 pathway and apoptosis module of the core TP53 transcriptional program [47,60]. ATF3 has context-dependent roles in tumorigenesis, cell death, and cell cycle arrest or senescence [61][62][63][64][65][66][67][68][69][70][71]. ATF3 is known to both activate and repress transcriptional activity, and it co-regulates chromatin at p53 target genes [60,72,73].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Activation Transcription Factor 3 (ATF3) is a stress-inducible transcription factor and member of the Hallmark p53 pathway and apoptosis module of the core TP53 transcriptional program [47,60]. ATF3 has context-dependent roles in tumorigenesis, cell death, and cell cycle arrest or senescence [61][62][63][64][65][66][67][68][69][70][71]. ATF3 is known to both activate and repress transcriptional activity, and it co-regulates chromatin at p53 target genes [60,72,73].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…We tested this hypothesis using our Kras wild-type, pancreas-specific Kdm6a -KO mice, namely Ptf1a Cre ; Kdm6a fl/fl , or Ptf1a Cre ; Kdm6a fl/Y (C- Kdm6a fl/fl or C-Kdm6a fl/Y ) ( Figure 12 A ), in a well-established, cerulein-induced, chronic pancreatitis model. 27 Mice were treated with cerulein for 2 weeks and then allowed to recover for 1 and 14 days ( Figure 12 B ). There was a significant and persistent weight loss in female C- Kdm6a fl/fl mice at both day 1 and day 14 of recovery compared with the wild-type Ptf1a Cre ; Kdm6a +/+ (C) mice ( Figure 12 C ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, VEGFA upregulation affects tumor progression caused by the induction of ER stress ( 18 ). In addition, a recent study in ATF3-deficient mice showed that loss of ATF3 prevents the initiation and progression of KRAS-mediated PDAC ( 19 ). Several studies have shown that elevated SLC7A5 expression predicts a poor prognosis in PDAC and is regarded as a potential biomarker ( 20 22 ).…”
Section: Discussionmentioning
confidence: 99%